Preliminary study of the growth variability of Vibrio parahaemolyticus in simulated gastric digestion fluids - Zhang, Zheng’ao; Wu, Qiong; Zhang, Zilong; Du, Haoran; Yang, Yixuan; Wei, Wenhui; Zhao, Yuyang; Wang, Xiaowei; Zhang, Minglu (Frontiers in Microbiology, 2026)
Vibrio parahaemolyticus may enter the viable but non-culturable (VBNC) state under specific stress conditions such as low temperature and acidic environments. In this study, we simulated gastric fluid digestion of V. parahaemolyticus followed by transfer into intestinal fluids, and monitored changes in culturable cell counts, ATP levels, and morphological changes. The objective was to investigate the effects of pH and treatment duration of simulated gastrointestinal fluids on the induction and resuscitation of the VBNC state. Results showed that after 120 min of digestion in gastric fluid at pH 2.5 with added glucose, the lowest number of bacteria were induced into the VBNC state (1.98 × 106 CFU/mL). In contrast, the highest VBNC induction occurred after 60 min of digestion in gastric fluid at pH 4.5 without glucose (1.26 × 107 CFU/mL). When V. parahaemolyticus was treated with gastric fluid at pH 4.5 with glucose, followed by 120 min digestion in intestinal fluid, the highest number of viable cells were resuscitated (1.68 × 107 CFU/mL). Moreover, prolonged exposure to intestinal fluid resulted in a greater number of resuscitated cells, accompanied by higher ATP levels compared with post-gastric fluid digestion. Microscopic observations revealed that most cells regained curved morphology, with elongated particle size and shape more similar to those of viable cells. These findings demonstrate that acidic gastric fluid environments can induce V. parahaemolyticus into the VBNC state, and that subsequent exposure to intestinal fluid promotes extensive resuscitation. Resuscitated cells released into the environment may pose potential risks to both ecological systems and human health. This study provides important evidence to inform prevention and control strategies for V. parahaemolyticus.